Türk Toplumunun Kültürel Belleği Bağlamında Orhun Abideleri’ni Yeniden Düşünmek: Taşın Bedeni ve Belleği / Reconsideration of Orhon Inscriptions in the context of Cultural Memory of Turkish Society: The Body and Memory of Stone - Demir, Sertaç Timur (Journal of History Culture and Art Research, 2017)
Abstract This paper aims to deal with the Orhon Inscriptions among the concepts and debates on cultural memory for the purpose of ‘remembering’, ‘adaptation’, ‘updating’ and ‘refunctionalising’ through the television documentary “Time Traveller: Following the Steps of the Turks”. What do the inscriptions tell us about today? What does deducing, analysing and developing a methodology for this provide to the national heritage under the titles of past, identity, belonging and memory? In this article, accordingly, cultural memory questions and suggestions are offered through the Orhon Inscriptions. Documents and documentaries, without doubt, are instruments of interpreting the past and projecting the future. This research is conceptual as well as methodological. In this respect, a minimal “cultural memory glossary” is fictionalised and thus a sort of conceptual ground is generated. Öz Bu çalışma, “Zaman Yolcusu Türklerin İzinde” televizyon belgeselinden hareketle kültürel bellek kavram ve tartışmaları arasında Orhun Abideleri’ni ‘hatırlama’, ‘uyarlama’, ‘güncelleme’ ve ‘kullanılır kılma’ amacıyla ele almayı hedeflemektedir. Bu abideler bugüne dair ne söylemektedir? Bunu çıkarımlamaya çalışmak, analiz etmek ve daha önemlisi bunun için bir metodoloji geliştirmek mazi, kimlik, aidiyet ve bellek gibi kültürel çalışmaların en önemli başlıkları adına millet mirasına ne sağlar? Bu makale, Orhun Abideleri üzerinden kültürel bellek önermeleri ve önerileri sunmaktadır. Belgeler ve belgeseller, hiç şüphesiz, geçmişi yorumlamanın ve geleceği öngörmenin en kritik enstrümanlarından biridir. Bu arayış içeriksel olduğu kadar metodolojiktir de. Bu eksende makalede, minimal bir “kültürel bellek terimler dizini” kurgulanmaya çalışılmış ve böylece benzer çalışmalar için bir tür kavramsal zemin oluşturulmuştur.